2020
DOI: 10.1093/jxb/eraa588
|View full text |Cite
|
Sign up to set email alerts
|

Rice transcription factor MADS32 regulates floral patterning through interactions with multiple floral homeotic genes

Abstract: Floral patterning is regulated by intricate networks of floral identity genes. The peculiar MADS32 subfamily genes, absent in eudicots but prevalent in monocots, control floral organ identity. However, how the MADS32 family genes interact with other floral homeotic genes during flower development is mostly unknown. We show here that the rice homeotic transcription factor OsMADS32 regulates floral patterning by interacting synergistically with E class protein OsMADS6 in a dosage-dependent manner. Furthermore, o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 90 publications
1
4
0
Order By: Relevance
“…Here, we provide the first evidence about the function of the TaAGL14 gene in an earlier reproductive stage in floral meristem activation in wheat, which may very likely be similar to OsMADS32 function in rice. TraesCS3B02G318300 was 4.5 fold more upregulated in "Kontrast" than in "Basalt", which is in line with the activator role of OsMADS32 in initiating the floral meristem and its role in the termination of floral meristem activity and repressing its reversion to vegetative meristem [76]. TaFT (QTL TaHd177), from Phosphatidylethanolaminebinding protein (PEBP), was exclusively detected in the DRS in leaves tissue.…”
Section: Taagl14 Activates the Floral Switch And Snp At Vrn3 Represse...supporting
confidence: 65%
See 1 more Smart Citation
“…Here, we provide the first evidence about the function of the TaAGL14 gene in an earlier reproductive stage in floral meristem activation in wheat, which may very likely be similar to OsMADS32 function in rice. TraesCS3B02G318300 was 4.5 fold more upregulated in "Kontrast" than in "Basalt", which is in line with the activator role of OsMADS32 in initiating the floral meristem and its role in the termination of floral meristem activity and repressing its reversion to vegetative meristem [76]. TaFT (QTL TaHd177), from Phosphatidylethanolaminebinding protein (PEBP), was exclusively detected in the DRS in leaves tissue.…”
Section: Taagl14 Activates the Floral Switch And Snp At Vrn3 Represse...supporting
confidence: 65%
“…The highlight result in the double ridge stage is the detection of the MADS-box transcription factor 32 in QTL TaHd054. MADSS32 wheat gene ( TraesCS3B02G318300 , SAM) is the ortholog of OsMADS32 that regulates floral patterning in rice and takes charge of floral meristem identity and initiation through interactions with multiple floral homeotic genes to sustain floral organ development [ 76 ]. BLAST results showed that the predicted protein of TraesCS3B02G318300 is identical by 99% with TaAGL14 , 98% with TaAGL15 in wheat , and 87% with OsMADS32 in rice .…”
Section: Discussionmentioning
confidence: 99%
“…Among these five classes, the E-class protein plays an essential role in binding the other four class proteins to regulate the development of various floral parts. In rice, the ABC(DE)-class genes are mainly composed of MADS-box gene family members, including four genes under class A, three genes under B-class, two genes under C-class, two genes under class D, and six genes under E-class [14,15]. These findings indicate that MADS-box genes play important roles in the regulation of flower development.…”
Section: Introductionmentioning
confidence: 95%
“…The family number of bHLH was the highest among the 58 categories (Figure 6). Besides, in view of the importance of MADS genes in plant floral organ development [14,15], their transcription levels were further analyzed based on the recently obtained transcriptome data of 'USO14 monoecious cultivars in our lab (unpublished). There were 47 genes encoding MADS transcription factors, of which 13 were highly expressed in male flowers (Figure 7).…”
Section: Identification and Analysis Of Tfsmentioning
confidence: 99%
“…Knockout of rice AGL6-like gene (OsMADS6) and down-regulation of TaAGL6 in wheat induced the generation of pistillodies (Ohmori et al 2009;Su et al 2019). Moreover, an increased number of pistils, which had been transformed from stamens, was also observed in about 52% of the owers of the strong mutant of OsMADS32 (cfo1-1), a monocot-speci c MADS-box gene, but not in its weak mutants (Hu et al 2021;Sang et al 2012;Wang et al 2015). Apart from oral homeotic MADS-box genes, other genes play important roles in pistil emergence and development.…”
Section: Introductionmentioning
confidence: 99%